What Is the Self? Imitation and Subjectivity in Blaise Pascal's Pensées - Wood, William (Modern theology, 2010)
I aim to develop a fully theological, yet still Pascalian account of human subjectivity. Exegetically, I argue that the Pensées themselves present two such accounts. The first account is a portrait of fallen subjectivity, selfhood under the reign of sin. The second account is a portrait of authentic subjectivity. This latter account is explicitly Christological and even Trinitarian. Constructively, I argue that Pascal's two accounts show that our subjectivity is performative and imitative: whether under sin or under grace, to be a self is to imitate God.